Peran Kepala Sekolah dalam Penilaian Kinerja Guru (PKG) di SDN 01 Sumber Rejeki Mataram Bandar Mataram - Asep Irawan (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2022)
The purpose of this study was to determine the role of the principal in Teacher Performance Assessment activities in order to improve the quality of educators in order to realize the school's vision and mission at Elementary School, Sumber Rejeki Mataram. This research use desciptive qualitative approach. Researchers collect data and analyze data where the data sources used are primary and secondary data using interview, observation, and documentation techniques. The results of this study are that the principal has several roles, namely as an innovator who triggers the PKG agenda, then the principal acts as a drafter and supervisor who makes the concept of activities from the beginning of the activity to the execution of the PKG program and finally as an evaluator, namely evaluating PKG activities, this can be seen from the activeness of the principal in overseeing activities in schools, especially those related to PKG activities. Some of the principal's roles encourage school principals to make breakthroughs and progressive policies to make PKG activities a success. The PKG activities that have been running since 2015-2016 have been beneficial in improving the quality of educators at Sumber Rejeki Mataram Elementary School, that's why the principal makes this activity one of the mandatory activities that must be followed by all educators at Elementary School Sumber Rejeki Mataram. The series of activities starting from debriefing to conducting evaluations is the principal's agenda in realizing the vision, mission and goals of Sumber Rejeki Mataram Elementary School